ANALISIS BUKU MUATAN TEMATIK INTEGRATIF, SCIENTIFIC APPROACH, DAN AUTHENTIC ASSESSMENT KELAS II SEKOLAH DASAR - Vera Yuli Erviana (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
This research aim to describe: (1) the integrative thematic content, (2) thescientific approach content, and (3) the authenthic assessment in the textbook ofCurriculum 2013. This research was content analysis using the qualitative approach.The data analysis techniques used consisted of unitizing, sampling, recording, inferring,and narrating. This results of this study are as follows. (1) Most of the integratedindicators in the textboox are not achieved because KD numbering error in accordancewith Permendikbud Number 67 Year 2013, and incomtability with KD material listed(2) The conten of the scientific approach in the textbook includes activities that vary,and direct the students to interact to build knowledge (3) The content of authenthicassessment already fulfils most of the indicators, but it still needs to be equipped withthe rubric to assist teachers in implementing the assessment. This assessment to describethe ability of the students from the aspects of attitude, knowledge, and skills.Keywords: thematic integrative, scientific approach, and authentic assessment, thetextbook of curricullum 2013